Adenosine isolated from Grifola gargal promotes glucose uptake via PI3K and AMPK signalling pathways in skeletal muscle cells. (June 2017) - Yoshioka, Yasukiyo; Harada, Etsuko; Ge, Danyao; Imai, Kunio; Katsuzaki, Hirotaka; Mishima, Takashi; Gabazza, Esteban C.; Ashida, Hitoshi
Highlights: Grifola gargal increased glucose uptake in skeletal muscles. Adenosine was identified as an active compound from Grifola gargal . Adenosine promoted GLUT4 translocation to membrane via AMPK and PI3K/Akt pathway. Abstract: Grifola gargal, an edible mushroom originating in southern Argentina and Chile, is known to have such beneficial health effects as antioxidant and anti-inflammatory activities. A low molecular weight fraction from Grifola gargal (GLF) decreased fasting blood glucose levels in high-fat diet-induced diabetic mice. This implicated Grifola gargal as a functional food to prevent type 2 diabetes mellitus (T2DM). To address the unknown underlying molecular mechanisms, we investigated, using L6 myotubes, whether GLF promoted GLUT4 translocation to the plasma membrane and its related signalling pathways. In addition, adenosine was isolated and identified the active compound in GLF to increase glucose uptake and promote GLUT4 translocation in L6 myotubes. Adenosine activated PI3K/Akt signalling and phosphorylation of AMPK, by binding to the adenosine receptor A1. Thus, Grifola gargal is a promising functional food to prevent post-prandial hyperglycaemia and T2DM by promoting glucose uptake in muscle.